2020
DOI: 10.1029/2020gl089373
|View full text |Cite
|
Sign up to set email alerts
|

Global Methyl Halide Emissions From Rapeseed (Brassica napus) Using Life Cycle Measurements

Abstract: Global budgets of methyl halides are not balanced between currently identified sources and sinks. Among biological sources, rapeseed is regarded as the second largest terrestrial source of CH 3 Br, extrapolated from laboratory-based incubations and limited field measurements. This study analyzes the CH 3 Br budget from rapeseed (Brassica napus "Empire"), using field-based life cycle measurements, yielding a globally scaled emission rate of 2.8 ± 0.7 Gg year −1. Though this verifies that rapeseed is a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Sample storage time in the syringe was less than 5 min. The air samples were cryotrapped and then cryo-focused prior to injection into a gas chromatograph-mass spectrometer (Agilent 6890 N/5973, Agilent Technologies, California, USA) for CH 3 Br and CH 3 Cl analysis 8 , 53 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample storage time in the syringe was less than 5 min. The air samples were cryotrapped and then cryo-focused prior to injection into a gas chromatograph-mass spectrometer (Agilent 6890 N/5973, Agilent Technologies, California, USA) for CH 3 Br and CH 3 Cl analysis 8 , 53 .…”
Section: Methodsmentioning
confidence: 99%
“…The initial headspace was filled with ambient air, either outdoor air or laboratory air. Headspace air samples from the jars were drawn into the sampling loop at 30 min intervals, and then drawn through a cryotrap, followed by desorption, cryofocusing, and injection into a gas chromatograph-mass spectrometer (Agilent 6890N/5973, Agilent Technologies, California, USA) for CH 3 Br and CH 3 Cl analysis 8 , 53 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…China is the third-largest producer of rapeseed in the world after the European Union and Canada, accounting for 12% of the total rapeseed production in 2015-2016, and the arable land lies mainly along the Yangtze River, which is suitable for growing rapeseed (Khir et al, 2017). Previous studies have reported that the global emissions of CH3Br by the rapeseed industry range from 2.8 ± 0.7 Gg yr -1 (Jiao et al, 2020) to 5 Gg yr -1 (Gan et al, 1998;Mead et al, 2008). Considering the proportion of eastern China in global rapeseed industry, the emissions of CH3Br by rapeseed in eastern China could be about 0.3-0.6 Gg yr -1 .…”
Section: Potential Of Anthropogenic Sources That Contribute To Ch3br Emissionsmentioning
confidence: 99%
“…In the life cycle of rapeseed, CH3Br is largely emitted during the flowering period in the 2 months after sowing (Jiao et al, 2020). Rapeseed in the northern hemisphere generally blooms in the warm weather from March to May.…”
Section: Potential Of Anthropogenic Sources That Contribute To Ch3br Emissionsmentioning
confidence: 99%